Using Video Modeling and Mobile Technology to Teach Social Skills. (January 2017) - Haydon, Todd; Musti-Rao, Shobana; McCune, Ashley; Clouse, Diane E.; McCoy, Dacia M.; Kalra, Hilary D.; Hawkins, Renee O.
There has been growing interest in the field of education regarding the use of technology in classrooms to improve student outcomes. Specifically, researchers have demonstrated positive outcomes for using mobile technology with students with autism spectrum disorder (ASD). Fewer studies have used mobile technology with students with emotional and behavioral disability (EBD). The purpose of this article is to discuss the effectiveness of video modeling as an intervention package and highlight the benefits of using video modeling and mobile technology to teach behavioral skills to students with EBD. The article provides guidelines and resources for teachers to implement video modeling instruction using mobile technology in the general education setting.